2022
DOI: 10.1158/1541-7786.mcr-22-0123
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of lncRNA152 as an Angiogenesis-Inhibiting Tumor Suppressor in Triple-Negative Breast Cancers

Abstract: Long non-coding RNAs have been implicated in many of the hallmarks of cancer. Herein, we found that the expression of lncRNA152 (lnc152; a.k.a. DRAIC), which we annotated previously, is highly upregulated in luminal breast cancer (LBC) and downregulated in triple-negative breast cancer (TNBC). Knockdown of lnc152 promotes cell migration and invasion in LBC cell lines. In contrast, ectopic expression of lnc152 inhibits growth, migration, invasion, and angiogenesis in TNBC cell lines. In mice, lnc152 inhibited t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Non-coding RNAs account for >90% of the entire human gene transcripts, participate in almost all epigenetic regulation, and play an important role in the complex life activities of advanced eukaryotes (16,17). Abnormal expressions of lncRNAs are involved in the process, metastasis, and prognosis of breast cancer (18)(19)(20). LncRNAs may play a role in promoting or inhibiting tumorigenesis and progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-coding RNAs account for >90% of the entire human gene transcripts, participate in almost all epigenetic regulation, and play an important role in the complex life activities of advanced eukaryotes (16,17). Abnormal expressions of lncRNAs are involved in the process, metastasis, and prognosis of breast cancer (18)(19)(20). LncRNAs may play a role in promoting or inhibiting tumorigenesis and progression.…”
Section: Discussionmentioning
confidence: 99%
“…acts as an angiogenesis inhibitor in triple-negative breast cancer that impedes cancer cell metastasis (20).…”
Section: Discussionmentioning
confidence: 99%
“…In most tumors, microvascular formation is a prognostic marker for metastasis, recurrence, and survival [ 24 , 25 ]. Angiogenesis-related genes have been reported to be potential prognostic markers associated with BC, and integrating these genes has important implications for understanding and assessing tumor progression [ 1 , 26 , 27 , 28 , 29 , 30 ]. Among these genes, lncRNAs also play an essential role [ 26 , 28 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Originally, LncRNA 152 was found to play an oncogenic role in prostate cancer. 24 Further studies have revealed that LncRNA 152 regulates cell proliferation, invasion, migration and autophagy, and is associated with a variety of cancers. 25,26 Besides, the expression of LncRNA 152 is positively associated with the disease-free survival in renal cell carcinoma patients.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA 152, also known as LncRNA DRAIC, is a 1.7 kb LncRNA located on human chromosome 15q23. Originally, LncRNA 152 was found to play an oncogenic role in prostate cancer 24 . Further studies have revealed that LncRNA 152 regulates cell proliferation, invasion, migration and autophagy, and is associated with a variety of cancers 25,26 .…”
Section: Introductionmentioning
confidence: 99%